Recovery in People with Schizophrenia (PwS) - Arum Septi Mawarni; Zainal Abidin; Ahmad Gimmy Prathama Siswadi (PSIKODIMENSIA, 2019)
The present study is aimed to find out the description of their recovery particularly those with residual type. This study was conducted in a mixed method using a descriptive design. Sample collection was conducted through purposive sampling, equipped with criteria of Residual Type PWS with age above 18 years old. Previously, testing of Recovery Assessment Scale (RAS) measuring instrument was conducted to 59 PWS, who were all outpatients. The result of this study reveals that using the method, PWS outpatients has a deemed high recovery rate, yet they still have constraints in dominant symptom factors.